Quark model with chiral-symmetry breaking and confinement in the Covariant Spectator Theory - Biernat, Elmar P. (2016)
We propose a model for the quark-antiquark interaction in Minkowski space using the Covariant Spectator Theory. We show that with an equal-weighted scalar-pseudoscalar structure for the confining part of our interaction kernel the axial-vector Ward-Takahashi identity is preserved and our model complies with the Adler-zero constraint for π-π-scattering imposed by chiral symmetry.